FAKTOR-FAKTOR YANG BERPENGARUH PADA PENDAPATAN USAHATANI TEMBAKAU RAJANGAN (Nicotiana tabacum) DI KABUPATEN BOYOLALI - Lintang, Aulia; Kusnandar, Kusnandar; Riptanti, Erlyna Wida (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
This study was conducted to determine the total farming costs, income, and revenue, as well as to identify the factors influencing the income of chopped tobacco farmers in Boyolali Regency. The research employed a descriptive-analytical method, with a purposive sampling technique for location selection. The sample consisted of 90 respondents, selected using the accidental sampling method. Multiple linear regression analysis and farm cost analysis were utilized in this study.  The results showed that farmers earned a revenue of IDR 103,148,355 per MT per hectare, with a total income of IDR 87,859,261 per MT per hectare. The farming costs incurred by farmers included implicit costs of IDR 3,947,792 per MT per hectare and explicit costs of IDR 15,289,093 per MT per hectare. Several factors partially influenced the income of chopped tobacco farming in Boyolali Regency, including land area, selling price, production quantity, and labor costs. However, fertilizer costs did not significantly affect farmers' income. Simultaneously, the independent variables had a significant impact on the income of chopped tobacco farming in Boyolali Regency. Among these variables, production quantity had the most significant influence on the income of chopped tobacco farmers in the region.